El cuento infantil y la lectura en el tercer grado de la escuela de Educación Básica “Alonso de Mercadillo”, periodo 2022-2023 - Encalada Paladines, Nayeli Jaquira (2023)
This research work was about Children's Tales and Reading , the main objective was to determine the influence that children's tales have on student ́s reading at "Alonso de Mercadillo" Elementary School, 2022-2023 school year; the specific objectives were: to diagnose the reading level in students of third grade; to apply an improvement proposal using children's tales as a didactic resource to strengthen reading skills and to evaluate the use of children's tales as a didactic resource to improve the reading process. To carry out this research study, the descriptive type of research was used, with a mixed approach and quasi-experimental design, during the process the scientific, statistical, analytical, synthetic and descriptive methods were applied. The techniques used were the interview that was designed to the teacher, in the same way the instruments used were the interview questionnaire that was applied to the teacher and a checklist to measure the reading level was applied to the students, the target population was "Alonso de Mercadillo" Elementary School, 28 students and one teacher were selected. The results of this study show that the main purpose of the use of children's tales is to enhance the reading process of students and strengthen the teaching method of the teacher, activities implemented in the improvement proposal, to improve their skills and abilities, because while children's tales are used just to entertain, they also provide values and significant learning, becoming one of the most valuable tools for the kids ́ education. Key words: Children's tales, skills, strategies, methodologies, reading, teaching - learning.